(untitled) (Annals of Medical Research, 2025)
Aim: The aim is to compare the characteristics of de nova metastatic BC (dnMBC) and recurrent metastatic BC (rMBC). Materials and Methods: The study included female patients diagnosed with histologically dnMBC and rMBC who received treatment at a tertiary care center from 2010 to 2019. Medical records were utilized to collect information regarding the patients’ tumors, alongside clinical and demographic characteristics. Each patient’s overall survival (OS) was determined starting from the moment they were diagnosed with MBC. The patients with dnMBC and rMBC were compared statistically based on their clinical and sociodemographic features. Results: Out of the 322 patients, 213 (66.1%) had rMBC, and 109 (33.9%) had dnMBC. Patients with dnMBC were older (p<0.001), and had a worse Eastern Cooperative Oncology Group Performance Score (p<0.001), a higher number of postmenopausal patients (p<0.001). Multicentricity/multifocality (p=0.017), human epidermal growth factor receptor 2 positivity (p=0.010), T-stage, N-stage (p<0.001), and tumor marker levels (p<0.05) showed significant differences between the groups. However, neither the median OS (29.0 months vs 21.0 months, respectively; p=0.152) nor the metastatic spread patterns (p>0.05) differed significantly between the groups. Conclusion: There was no difference in OS. Clinic subtype, tumor grade, and treatment modalities may confuse the survival outcomes in BC patients.